2021
DOI: 10.1590/18094449202100630001
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Migrant Women as Killjoys: Disclosing Racism in “Friendly” Portugal

Abstract: Resumo Neste artigo, colocamos a noção de Sarah Ahmed de “estraga-prazeres feminista” em diálogo com estudos feministas de migração e decoloniais. Temos como objetivo analisar como o ativismo digital das mulheres brasileiras em Portugal se torna um “coletivo estraga-prazeres feminista”, desafiando a construção das brasileiras como um “corpo colonial”, bem como a narrativa de ser Portugal um país não racista. Guiado pela abordagem decolonial feminista e fazendo uso da etnografia virtual, junto de uma entrevista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Most immigrants living in Portugal are from the CPLC community, with Brazilian immigrants currently being the most representative group (Posch & Cabecinhas, 2020). According to the study by Godinho et al (2008) on African and Brazilian immigrant's mental health, Brazilians are more prone to mental health problems, especially Brazilian women, which can be explained by the literature revealing higher levels of prejudice and discrimination towards them in Portugal, contributing to undermining their well-being (França & Oliveira, 2021). With the outbreak of COVID-19, Posch and Cabecinhas' (2020) qualitative research on the mental health of Brazilian immigrants showed that the pandemic amplified the number of challenges these immigrants had to face (e.g., unemployment) and intensified their feelings of loneliness.…”
Section: Migration In Portugal: Health Challenges and The Burden Of C...mentioning
confidence: 99%
“…Most immigrants living in Portugal are from the CPLC community, with Brazilian immigrants currently being the most representative group (Posch & Cabecinhas, 2020). According to the study by Godinho et al (2008) on African and Brazilian immigrant's mental health, Brazilians are more prone to mental health problems, especially Brazilian women, which can be explained by the literature revealing higher levels of prejudice and discrimination towards them in Portugal, contributing to undermining their well-being (França & Oliveira, 2021). With the outbreak of COVID-19, Posch and Cabecinhas' (2020) qualitative research on the mental health of Brazilian immigrants showed that the pandemic amplified the number of challenges these immigrants had to face (e.g., unemployment) and intensified their feelings of loneliness.…”
Section: Migration In Portugal: Health Challenges and The Burden Of C...mentioning
confidence: 99%